2014
DOI: 10.4238/2014.july.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and functional characterization of a novel CBL-interacting protein kinase NtCIPK2 in the halophyte Nitraria tangutorum

Abstract: ABSTRACT. CBL-interacting protein kinases (CIPKs) mediate many plant responses to abiotic stress. However, their functions are poorly understood in halophytes. In this study, we isolated a CIPK gene, NtCIPK2, from the halophyte Nitraria tangutorum. By sequence alignment and the construction of a phylogenetic tree, we found that NtCIPK2 is similar to CIPK2 proteins from other plants, and contains conserved domains and motifs. The promoter of NtCIPK2 harbors many cis-acting elements that might be recognized and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Whether CIPK2 really possesses a significant role in the wild-type plant cell response to salt stress, however, remains unknown. Our findings showing that overexpression of AtCIPK2 and HsCIPK2 in Arabidopsis transgenic plants significantly enhances the tolerance of seed germination and plant growth to NaCl stress, together with the previous finding that expression of halophytic shrub NtCIPK2 in E. coli cells enhances host cell tolerance to salt toxicity (Zheng et al 2014), demonstrate that CIPK2 plays a significant role in plant salt tolerance. In addition, we also noticed that, based on seedling growth phenotype, the wild-type seedlings appear to be more sensitive to NaCl on 0.5× MS agar plates (1 % sucrose) in our study than on 1× MS agar plates (2 % sucrose) in the previous studies (Guo et al 2004, Li et al 2012.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Whether CIPK2 really possesses a significant role in the wild-type plant cell response to salt stress, however, remains unknown. Our findings showing that overexpression of AtCIPK2 and HsCIPK2 in Arabidopsis transgenic plants significantly enhances the tolerance of seed germination and plant growth to NaCl stress, together with the previous finding that expression of halophytic shrub NtCIPK2 in E. coli cells enhances host cell tolerance to salt toxicity (Zheng et al 2014), demonstrate that CIPK2 plays a significant role in plant salt tolerance. In addition, we also noticed that, based on seedling growth phenotype, the wild-type seedlings appear to be more sensitive to NaCl on 0.5× MS agar plates (1 % sucrose) in our study than on 1× MS agar plates (2 % sucrose) in the previous studies (Guo et al 2004, Li et al 2012.…”
Section: Discussionsupporting
confidence: 80%
“…Overexpression of Zea mays ZmCIPK16 or Hordeum brevisubulatum HbCIPK2 in Arabidopsis sos2 mutants improves their tolerance to salt and/or osmotic stresses (Zhao et al 2009, Li et al 2012. Furthermore, expression of halophytic shrub (Nitraria tangutorum) NtCIPK2 in Escherichia coli improves cell tolerance to high salinity, alkalinity, osmotic stress, dehydration, heat, and cold stresses (Zheng et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that Nitraria may adapt to abiotic stress conditions through increased antioxidant enzyme activities, proline accumulation, level of soluble carbohydrates and reduced the intracellular Na + / K + ratio [7,[10][11][12][13]. However, the molecular mechanisms underlying the physiological adaptability of N. tangutorum to various stresses need further study [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the differentially induced expression of OsCIPK genes by different abiotic stresses was proposed to be responsible for improved stress tolerance in rice 10 . It was also reported that the overexpression of halophytic gene, NtCIPK2 in Escherichia coli resulted in better bacterial growth under high salinity and osmotic conditions, in addition to dehydration and extreme temperatures compared to control 11 . More recently, it was reported that the overexpression of GhCIPK6 significantly enhanced the tolerance to salt, drought and ABA stresses in transgenic Arabidopsis 21 .…”
Section: Primersmentioning
confidence: 99%
“…increase the Ca 2+ concentration in cell cytoplasm, which acts as a major secondary messenger to transduce the extracellular stimuli 2 [6][7][8] . Although there are many reports on the role of CIPKs in imparting abiotic stress tolerance [9][10][11] , there could be vast diversity in the functions exhibited by different CIPKs. This could be attributed to the superior nucleotide/ polypeptide assembly existing in different CIPKs, making them functionally more efficient 12,13 .…”
mentioning
confidence: 99%